Islamic Counseling Guidance Sumang Indigenous Cultural Wisdom in Spiritual Values ​​to Minimize Violations of Islamic Shari'a - sahriza sahriza (At-Taujih : Bimbingan dan Konseling Islam, 2021)
Abstrak Sumang value is related to Islamic values, because it has spiritual values and ornate on ahlakkul karimah, maintaining self, dignity and dignity of family and society in general. The method used is qualitative deskreptif method The location of this research was conducted Kenawat Village, numbering five people, JD as Reje Kampung (village head), SR as petue (traditional figure), IN as banta (village sectarian), and KR as Imem Kampung (village imam). In this study, the object is a person who has committed adultery and was arrested by two families (SZ and ND) (MD and RV) who were married first under the age of 19 and under and one family aged 20 years. As a result, there needs to be good communication with parents, and the whole community. It is very embarrassing for the family and the whole community of kenawat village. Efforts have been made apparatus that has opened payrolls for teenagers. The ngaji program for children in TPA every afternoon. And the study for teenagers and adults is held once a week every Friday night. This is one of the programs created by the village apparatus in minimizing violations of Islamic Law. The obstacles faced by the village apparatus are two factors internally and externally. Internal factors are less understanding of the apparatus to formulate a qanun in the village. And the lack of understanding of Islamic sharia law and Gayo customary law. External factors Need direct socialization conducted by the central Aceh government so that qanun in this village can be carried out properly.Keywords: Sumang; Culture: Islamic Shariah.